The History of British Women's Writing, 1690 - 1750 Volume Four - Ballaster, R.; Ballaster, R. (History of British Women's Writing, 2010)
This volume charts the most significant changes for a literary history of women in a period that saw the beginnings of a discourse of 'enlightened feminism'. It reveals that women engaged in forms old and new, seeking to shape and transform the culture of letters rather than simply reflect or respond to the work of their male contemporaries.